Implications of disturbed photon‐counting statistics of Eiger detectors for X‐ray speckle visibility experiments. (23rd July 2019) - Möller, Johannes; Reiser, Mario; Hallmann, Jörg; Boesenberg, Ulrike; Zozulya, Alexey; Rahmann, Hendrik; Becker, Anna-Lena; Westermeier, Fabian; Zinn, Thomas; Zontone, Federico; Gutt, Christian; Madsen, Anders
Abstract : It is demonstrated that small errors in the photon statistics of a photon‐counting area detector can be identified and corrected for. This is of crucial importance for low‐count‐rate X‐ray speckle visibility experiments where the photon statistics of coherent scattering images are characterized to obtain information about the sample's dynamics. Abstract : This paper reports on coherent scattering experiments in the low‐count regime with less than one photon per pixel per acquisition on average, conducted with two detectors based on the Eiger single‐photon‐counting chip. The obtained photon‐count distributions show systematic deviations from the expected Poisson–gamma distribution, which result in a strong overestimation of the measured speckle contrast. It is shown that these deviations originate from an artificial increase of double‐photon events, which is proportional to the detected intensity and inversely proportional to the exposure time. The observed miscounting effect may have important implications for new coherent scattering experiments emerging with the advent of high‐brilliance X‐ray sources. Different correction schemes are discussed in order to obtain the correct photon distributions from the data. A successful correction is demonstrated with the measurement of Brownian motion from colloidal particles using X‐ray speckle visibility spectroscopy.